Rare association of xeroderma pigmentosum with ovarian Sertoli–Leydig cell tumor: A case report and literature review - Pal, Anwesa; MAHAPATRA, MANORANJAN; TALUKDER, ANIRBAN; NAYAK, MAMITA; Mohapatra, Janmejaya; PADHY, ASHOK KUMAR; ROUT, NIHAR RANJAN (Indian Journal of Case Reports, 2026)
Xeroderma pigmentosum (XP) is a rare autosomal recessive disorder caused by deoxyribonucleic acid repair defects, predisposing patients to early cutaneous malignancies and, less frequently, internal tumors. We report the case of a 19-year-old female with XP who presented with abdominal pain, distension, and secondary amenorrhea for 3 years. Imaging revealed a large solid-cystic ovarian mass with elevated CA-125. She underwent fertility-sparing staging laparotomy, and histopathology confirmed a well-differentiated Sertoli–Leydig cell tumor of the ovary (Federation of Gynecology and Obstetrics Stage IA). No adjuvant treatment was required. She remains disease-free after 18 months, with restoration of normal menstruation. This rare association emphasizes close surveillance in XP patients for early detection of internal malignancies.